Perbedaan Kadar Sgot Dan SGPT Pada Tikus (Rattus Norvegicus) Yang Diberi Paparan Asap Rokok Herbal Dan Asap Rokok Konvensional - Ferdian, Ricky; , dr. Retno Sintowati, M.Sc; , dr. Ratih Pramuningtyas, Sp.KK (2015)
Background : Cigarettes were sources of free radicals, if it taken into the body continuously body cells will undergo oxidative stress ended cell damage with no exception for liver cells. Damage to liver cells will lead to increased levels of AST and ALT. Objective : This study was to determine differences in the levels of AST and ALT in rats (Rattus norvegicus) were given exposure to herbal and conventional cigarette. Methodology : Experimental laboratory, study design with pretest-posttest control group design. Samples ware 18 male rats were randomly divided into 3 groups. Negative control group, the conventional treatment group 1 cigarette smoke exposure and treatment 2 herbal cigarette smoke exposure. The results of each group were calculated using Oneway ANOVA and Post Hoc test continued. Results : Based on the ANOVA test results obtained significant probability value, the value of the levels of SGPT and SGOT p = 0.00 p = 0.001 thus p <0.05 then the three groups have different levels of SGOT and SGPT significantly. Then the LSD test to compare each group showed ALT levels K - P1, K - P2, P1 - K, P1 - P2 and P2 - K there is a significant difference. While comparisons between groups were not significant P2 - P1. LSD test for the data obtained SGOT K - P1, P1 - K, P1 - P2 and P2 - P1 there is a significant difference. While K - P2, P2 - K insignificant. Conclusion : There were differences increasing levels of AST and ALT in rats (Rattus norvegicus) that given to herbal and conventional cigarette smoke. Which was the increasing levels of AST and ALT from conventional were higher than herbal cigarette.